Influence of apical patency on root canal treatment outcome: a contemporary overview - Almohareb, Rahaf; Barakat, Reem; Alshedokhi, Aljohara (Journal of Stomatology, 2021)
Determining the apical limit of root canal preparation has proved to be a matter of continuous debate. During root canal instrumentation, soft tissue or debris get impacted in the apical region causing canal blockage. This can be avoided if apical patency is maintained. A major concern over apical patency is extrusion causing periapical tissue irritation and delaying or hindering periapical healing. The aim of this review was to evaluate the literature regarding the influence of apical patency on success of root canal treatment. A search of the literature was conducted via PubMed using the terms “apical patency” OR “patency file”. Inclusion criteria were: articles published in English, between the years 2000 and 2020, and were neither case reports nor reviews. A total of 32 articles were selected. Clinical studies directly investigating the influence of apical patency on root canal treatment outcome are limited. In-vitro and in-vivo studies were found evaluating amount of extrusion, canal cleanliness, and shaping associated with apical patency examined this influence indirectly. According to the available literature, there is little evidence to contraindicate the use of apical patency or suggest it has a negative effect on root canal treatment outcome. However, more evidence of high quality is required to confirm this.